2016
DOI: 10.1002/cbm.2005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a community mental health initiative on outcomes for offenders with a serious mental disorder

Abstract: Provision of specialised community mental health services for higher-risk male offenders with a mental disorder may reduce recidivism in the short and longer term - within 3 months and up to 4 years respectively. Statistical modelling also pointed to the need to include treatment for substance abuse and assistance in identifying stable accommodation and brokerage of community services among the interventions and services. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
(22 reference statements)
0
30
0
Order By: Relevance
“…In addition, we suggest a focus on individual-level strategies to improve health on release, which should be developed in collaboration with people with lived experience and with evaluation of acceptability, accessibility, and effectiveness. Building on evidence from transitional programs [30][31][32][33][34][35][36], concrete solutions may include comprehensive and patient-focused discharge planning before release from jail, the provision of information in jail and in the community on health issues and community-based services, and enhancement of programs to link people in custody with services in the community, including primary care. After release, emphasis should be placed on supports that have the capacity to adapt and respond to people's changing circumstances and needs, including harm reduction and substance use disorder treatment programs such as opioid agonist treatment programs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we suggest a focus on individual-level strategies to improve health on release, which should be developed in collaboration with people with lived experience and with evaluation of acceptability, accessibility, and effectiveness. Building on evidence from transitional programs [30][31][32][33][34][35][36], concrete solutions may include comprehensive and patient-focused discharge planning before release from jail, the provision of information in jail and in the community on health issues and community-based services, and enhancement of programs to link people in custody with services in the community, including primary care. After release, emphasis should be placed on supports that have the capacity to adapt and respond to people's changing circumstances and needs, including harm reduction and substance use disorder treatment programs such as opioid agonist treatment programs.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted one focus group at each of three community-based organizations in September and October 2018: a men's homeless shelter, a mental health service organization, and a social service agency providing voluntary and court-ordered programs for people with substance use disorders. The focus group guide (S1 File) was developed by three project team members (Catherine Hu, Jessica Jurgutis, and Fiona Kouyoumdjian) based on the study objectives and issues identified in previous research [36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the provision of mental health services is not commonplace in the majority of correctional facilities worldwide, we found that untreated mental illness was associated with a much lower likelihood of linkage to HIV care, while treated mental illness was associated with an increased likelihood of linkage, underscoring the need for such services in correctional facilities, particularly for those with concomitant chronic conditions. Ensuring continuity of care for people with mental health disorders has also been shown to reduce the rate of re‐incarceration, thereby helping to address another barrier to linkage to care. Finally, we found an association between age and linkage to care, whereby released inmates less than 30 years of age were much less likely to link to HIV care even after controlling for other risk factors, suggesting that greater attention be paid to younger inmates at the time of discharge.…”
Section: Discussionmentioning
confidence: 99%